Recent advances and practical challenges in the research of decellularized matrices for the fabrication of tiny-diameter artificial arteries - Yan Liu; Can Cheng; Jiaqi Xing; Zhaoxi Deng; Xu Peng (Collagen and Leather)
Abstract Despite advances in synthetic vascular grafts, replicating the dynamic biological functions of native microvasculature remains a critical challenge in cardiovascular tissue engineering. While polymer-based conduits offer scalability and dimensional versatility, the inherent bioinert nature leads to high failure rates in < 6 mm diameter applications due to thrombotic complications and mechanical mismatch with host tissue. Decellularized matrices (dECM) scaffolds emerge as a biologically strategic alternative, preserving crucial vascular basement membrane components and biomechanical cues through collagen/elastin retention. The present review systematically elaborates the research advancements, critical determinants, and practical challenges in utilizing dECM for tiny-diameter artificial vessels (inner diameter < 3 mm), while proposing three forward-looking solutions to address clinical translation barriers: (1) matrix optimization strategies through diameter-specific compliance matching and elastin reconstitution; (2) sterilization and preservation protocols preserving structural integrity with controlled immunogenicity; (3) immunomodulatory engineering via macrophage polarization regulation. The proposed methodologies establish innovative avenues for the engineering and clinical transplantation of tiny-diameter artificial vessels. Graphical abstract